2005
DOI: 10.1074/jbc.m406607200
|View full text |Cite
|
Sign up to set email alerts
|

RGS12 Interacts with the SNARE-binding Region of the Cav2.2 Calcium Channel

Abstract: Activation of GABA B receptors in chick dorsal root ganglion (DRG) neurons inhibits the Ca v 2.2 calcium channel in both a voltage-dependent and voltage-independent manner. The voltage-independent inhibition requires activation of a tyrosine kinase that phosphorylates the ␣ 1 subunit of the channel and thereby recruits RGS12, a member of the "regulator of G protein signaling" (RGS) proteins. Here we report that RGS12 binds to the SNARE-binding or "synprint" region (amino acids 726 -985) in loop II-III of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Consistent with this evidence, the long form of RGS12, through its PTB domain, is capable of direct, neurotransmitter-dependent interactions with the tyrosine-phosphorylated N-type calcium channel in primary dorsal root ganglion neurons (Schiff et al, 2000;Richman et al, 2005). The differential expression patterns of RGS12 splice variants in the embryo support our hypothesis that these proteins may serve a significant role in signal modification and scaffolding, presumably allowing specific subsets of signaling proteins to interact in specific locations during development.…”
Section: Fig 4 Expression Of Regulator Of G-protein Signaling (Rgs)supporting
confidence: 66%
See 1 more Smart Citation
“…Consistent with this evidence, the long form of RGS12, through its PTB domain, is capable of direct, neurotransmitter-dependent interactions with the tyrosine-phosphorylated N-type calcium channel in primary dorsal root ganglion neurons (Schiff et al, 2000;Richman et al, 2005). The differential expression patterns of RGS12 splice variants in the embryo support our hypothesis that these proteins may serve a significant role in signal modification and scaffolding, presumably allowing specific subsets of signaling proteins to interact in specific locations during development.…”
Section: Fig 4 Expression Of Regulator Of G-protein Signaling (Rgs)supporting
confidence: 66%
“…In addition to the RGS/RBD/GoLoco domain core, the long RGS12 splice variant has an N-terminal PDZ (PSD-95/Dlg/ZO-1) domain capable of binding the interleukin (IL) -8 receptor B (CXCR2) or its own C-terminus (Snow et al, 1998) and a phosphotyrosinebinding (PTB) domain that associates with tyrosine-phosphorylated N-type calcium channels (Schiff et al, 2000;Richman et al, 2005). Therefore, RGS12, in at least one isoform, may also mediate tyrosine kinase-dependent regulation of calcium channels and coordinate this regulation with Gprotein signals.…”
Section: Introductionmentioning
confidence: 99%
“…430 RGS12 interacts with both N-type and Ca(v)2.2 Ca 2+ channels and also binds a C-terminal motif found in proteins such as the IL-8 receptor. [39][40][41] We observed a  5-fold change in RGS12 mRNA expression between non-laboring and laboring myometrium. Western blotting demonstrated expression of RGS12 in human myometrial smooth muscle cells and immunofluorescence microscopy localized it to the cell cytoplasm.…”
Section: 27mentioning
confidence: 75%
“…However, RGS proteins have several other modes of action 172 including some that dimerize with Gβ 5 subunits and some (e.g., RGS12) that directly interact with Ca V 2.2 channels. 86,173 Experimental manipulation of RGS expression has been demonstrated to alter calcium channel inhibition 174,175 and it has also been shown that this in turn can alter short term synaptic plasticity. 176 Expression of several RGS proteins can be dynamically regulated by physiological and pathophysiological situations.…”
Section: Acknowledgementsmentioning
confidence: 99%